Strategi Pengorganisasian Masyarakat oleh Yayasan Srikandi Lestari dalam Mengampanyekan Isu Perubahan Iklim - Ade Indah Hutasoit; Hairani Siregar (Yayasan Literasi Sains Indonesia, 2025)
Coal-fired power plants are one of the biggest contributors to climate change. The environmental impacts of coal-fired power plant emissions are felt most by communities that depend on natural resources. NGOs act as a counterweight and controller of government development through a community-oriented approach to create equitable and sustainable change. Research on community organizing strategies related to the campaign on climate change issues, especially the rejection of PLTU, is still limited in scientific studies. Strategy has a crucial role for organizers. Without strategy, ideology and commitment will only become mere discourse without real action. The research aims to analyze the community organizing strategy carried out by Yayasan Srikandi Lestari. The research is expected to be a further consideration in the discovery of scientific concepts in the field of social welfare related to community organizing. The research used descriptive qualitative methods with interviews, observation, and documentation. The informant selection technique in this study used purposive sampling, involving 1 key informant, 5 main informants, and 2 additional informants. Data analysis techniques include data reduction, data display, and conclusion drawing. The results show that the foundation's strategy is to combine three approaches, namely locality development, social planning and social action through the stages of assessment, planning, implementation and evaluation, with participatory and humanist principles. The form of the campaign includes a social media campaign and direct action in the field that involves the affected community directly. The research recommends the implementation of engagement and termination stages to strengthen community independence in environmental advocacy.